HIV-positive youth who are perinatally infected have impaired endothelial function. (10th September 2017) - Dirajlal-Fargo, Sahera; Sattar, Abdus; Kulkarni, Manjusha; Bowman, Emily; Funderburg, Nicholas; McComsey, Grace A.
Abstract : Objective: Evaluating cardiovascular disease risk in children and youth 13 to 24 years old who are facing a life time exposure to both HIV and antiretroviral therapy is a research priority. This study compares endothelial function measured by peripheral arterial tonometry in HIV-positive youth infected perinatally and behaviorally as well as HIV-negative controls. Methods: Three groups of participants aged 8–30 year were enrolled; HIV-positive perinatally infected, HIV-positive behaviorally infected on antiretroviral therapy with HIV-1 RNA less than 1000 copies/ml, and HIV-negative controls. We measured the reactive hyperemic index, a measure of endothelial function, using endoPAT (Caesarea, Israel). Markers of systemic inflammation, monocyte activation, and gut integrity were also assessed. Spearman correlations and regression analyses were used to explore relationships between endothelial function measures and other measured variables. Results: Overall, 119 participants were enrolled: 53 HIV-positive behaviorally infected, 18 HIV-positive perinatally infected, and 48 controls. Overall, 71% were men; 77% African Americans and median age was 22 years old. Median (interquartile range) reactive hyperemic index was lower in the HIV-positive perinatally infected group [1.34 (1.20, 1.42)], compared with the behaviorally infected group [1.52 (1.34, 1.75)] and the control group [1.52 (1.27, 1.80; P  < 0.01)]. Soluble CD14, a marker of monocyte activation, intestinal fatty acid-binding protein, a marker of gut integrity and soluble vascular cell adhesion molecule, a marker of vascular dysfunction, were different among the three groups ( P  ⩽ 0.01). Conclusion: HIV-positive youth infected perinatally appear to have higher levels of endothelial dysfunction and immune activation when compared with behaviorally infected youth. Further longitudinal studies are needed to determine whether perinatally infected youth have higher risks of cardiovascular disease.